Shared Mental Models, Catch-up Development and Economic Policy-Making: The Case of Germany after World War II and Its Significance for Contemporary Russia - Joachim Zweynert (Hamburg Institute of International Economics (HWWA), 2004)
The paper deals with the connection between politically induced catch-up development, cultural and intellectual traditions and economic order in Germany and Russia. It is argued that in the history of both countries we encounter significant structural parallels, including the totalitarian experience. After World War II the German political élite managed to implement capitalism in a country, the population of which was still hostile towards capitalism. The key to success was that the German political rulers, in contrast to the Russian ,,young reformers“ of the early 1990s, from the beginning on took into account the shared mental models prevailing in Germany. Therefore some lessons may be drawn from the German historical experience in regard to today's Russia.
Keywords: P51; B25; Z10; 330; Cultural Economics; Economic Development; Transition; Totalitarianism; Wirtschaftsethnologie; Wirtschaftssoziologie; Systemtransformation; Übergangswirtschaft; Entwicklungskonvergenz; Kriegsschaden; Deutschland; Russland